ANALYSIS OF THE INFLUENCE OF LEADERSHIP STYLE, WORK MOTIVATION, ORGANIZATIONAL CULTURE, AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PT BANK SYARIAH INDONESIA, TBK PEKALONGAN WAHID HASYIM BRANCH OFFICE - Intania Hafazha Fajrin; Muhammad Asrori; Nur Maziyah Ulya (Politeknik Negeri Semarang, 2023)
This study aims to analyze the significance of the influence of leadership style, work motivation, organizational culture, and work discipline on employee performance at PT Bank Syariah Indonesia, Tbk Pekalongan Wahid Hasyim Branch Office either simultaneously or partially. The population in this study were all employees at PT Bank Syariah Indonesia, Tbk Pekalongan Wahid Hasyim Branch Office. The sampling technique used saturated sampling, namely as many as 45 employees. The data used in this study are primary data obtained through distributing questionnaires. The data analysis model uses a multiple linear regression analysis model. While the data analysis technique used the F statistical test, the coefficient of determination (R2), and the t statistical test which were processed using the SPSS 25.00 program. The results of the analysis and discussion show that leadership style, work motivation, organizational culture, and work discipline simultaneously have a significant effect on employee performance at PT Bank Syariah Indonesia, Tbk Pekalongan Wahid Hasyim Branch Office. Partially, work motivation, organizational culture, and work discipline have a positive and significant effect. Meanwhile, leadership style has a negative and insignificant effect on employee performance at PT Bank Syariah Indonesia, Tbk Pekalongan Wahid Hasyim Branch Office.